Structure Equation Modeling of Factors Affecting Export Performance of Weaving Sector of Pakistan - Allah, Dad; Asif, Mahbub Karim; Nadia, Farhana; Hock, Oo Yu (The Mattingley Publishing Co., Inc., 2020)
accounts for the nearly 55% share of the total economy. Major exports from textiles are yarns, raw and finished fabrics and also a limited quantity of value-added textile items. However, from the last one-decade, the textile industry is facing a lot of problems in terms of getting and maintaining export orders. Due to this Pakistani Textile Industry losing its competitiveness day by day resulting loss in millions of US Dollars per years. The raw woven fabric manufacturing sector lies almost in the middle of the supply line having a share of 8% in world exports. Its performance is significant for next value chain. This sector is also facing challenges in maintaining and improving its export rate which reduced from around 2.9 to 1.9 Billion US$ in 2017 whereas world market demand is increasing. Hence deprived performance ultimately losing its competitiveness. For this internal, external factors considered as independent variables and textile Business policy as a mediator variable together taken in order to know the impact on dependent variable export performance measured in percentage. Their relationship was analyzed by using Structural equation model and found eight factors are significant at confidence internal level of 90%. The government policy showed a significant mediation effect on export performance against eight independent variables which indicated its positive role in export activities. The recommendations in terms of new product development such as tri-axial woven, multilayer innovative fabrics, new markets, fulfillment of government promises thru policy are suggested for improving export rate and remains valid for long time.